A robustness test of asset pricing models using individual security returns - Limkriangkrai, M.; Durand, Robert; Watson, I. (Routledge, Taylor and Francis Ltd, 2009)
Tests of asset-pricing models typically form portfolios of stocks (based oncriteria such as market capitalization and book-to-market values). Thevalidity of this approach has been debated (see, for example, Berk, 2000).We consider a simple method of testing asset-pricing models using thereturns of individual securities and illustrate the approach in a test of therobustness of analyses reported by Durand et al. (2006) and Limkriangkraiet al. (2008).